Evaluation and Supervision of The Learning Process as An Effort to Improve Teacher Professionalism in Schools - Sari, Ratna Puspita; Yusron, Ali; Hidajat, Arif; Laoli, Adieli; Pasongli, Hernita (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The purpose of this study was to examine the evaluation and supervision of the learning process as an effort to increase teacher professionalism in schools. The method used is a qualitative research method with a type of field research. The research locations in this study were MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz, MAN 1 Jember, and MAN 2 Jember. The findings in this study are that, in general, the implementation of academic supervision at MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz, MAN 1 Jember, and MAN 2 Jember has been going well. School supervisors have an adequate understanding of academic supervision and can carry out their supervisory duties and functions properly. Second, there are still limitations in the aspects targeted for academic supervision by Madrasah supervisors at MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz. Not all aspects of academic supervision are the focus of school supervisors. Whereas in MAN 1 Jember and MAN 2 Jember, all aspects have been carried out by the madrasa supervisor. Supervised aspects include lesson planning, teaching and learning implementation, class management, and follow-up on learning outcomes. Third, Madrasa supervisors have developed various academic supervision techniques that are quite varied at MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz, MAN 1 Jember, and MAN 2 Jember. The techniques used include individual supervision, such as class visits, observations, and individual meetings; group supervision, such as teacher meetings/supervision meetings, committees, and group work, as in the MGMP. The approaches used in supervision activities include the official, partner, and family approaches.